Perancangan Purwarupa Pengukur Kadar Air dan Kualitas Pangan Komoditas Beras dan Jagung Menggunakan Sensor Kapasitif - Firmansyah, Dudi; Rahmawati, Riski Amalia; Firmansyah, Vera; Gianto, Gianto; Sutanto, Willi; Waras, Nandang Gunawan Tunggal; Yasri, Budi; Muslim, Azis; Irwanto, Decky Ari; Karsono, Eko; Alam, Hilman Syaeful; Sanjaya, Ari Susandy (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2024)
Water content is an indicator that can affect food quality and safety as well as commodity prices. Therefore, measuring the moisture content of commodities is important to ensure the food system viability. The development of increasingly sophisticated technology has led many companies to introduce water content measuring instruments called Moisture Content Meters (MCM). However, this tool is marketed at an expensive price. In this research, a prototype for measuring the moisture content and food quality of rice and corn commodities using a cheap capacitive sensor has been successfully made according to the design. Based on the testing results, this prototype has an accuracy value of 98,9%, precision of 97,4%, and error of 1,1%. The test results show that this prototype is accurate enough to measure the moisture contents of rice and corn samples, accompanied by consistent food quality indications according to applicable quality standards.